Answer:
Therefore x=9
Step-by-step explanation:
Give that,
log x+ log (x-3) = log 54
log x(x-3) =log 54 [
]
x(x-3) = 54
Now expand the above equation to get a quadratic equation
x²-3x=54
⇒x²-9x+6x-54=0
⇒x(x-9)+6(x-9)=0
⇒(x-9)(x+6)=0
⇒x-9=0 or, x+6=0
⇒x=9,-6
Now putting x= -6 in the given expression,
log(-6)+log(-6-9)=log 54.
Since log (-6) does not exist.
Therefore x=9
X=-4 that might be the correct awnser
Answer:
7/10
Step-by-step explanation:
What do we complete there is no picture
Answer:
£2,120.00
Step-by-step explanation:
First, converting R percent to r a decimal
r = R/100 = 3%/100 = 0.03 per year.
Solving our equation:
A = 2000(1 + (0.03 × 2)) = 2120
A = $2,120.00
The total amount accrued, principal plus interest, from simple interest on a principal of £2,000.00 at a rate of 3% per year for 2 years is £2,120.00.